1988
DOI: 10.1002/bms.1200160157
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic/mass spectrometric quantitative analysis of eicosanoids in human oesophageal mucosa

Abstract: In order to investigate the contribution of eicosanoids to human oesophageal functions and disorders (gastrooesophageal reflux, GOR and reflux oesophagitis, RO), we have used a selected ion monitoring gas chromatographic/mass spectrometric methodology to quantify the cyclooxygenase and lipoxygenase products biosynthesized in vitro by endoscopic mucosal biopsy specimens. Prostaglandins (PGs) were quantified as MEMOTMS derivatives and HETEs, as hydrogenated methyl ester of tert-butyldimethylsilyl) ether derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…7 In the human esophagus, however, the main pathway for prostaglandin (PG) synthesis is reported to involve lipoxygenase rather than cyclooxygenase. 15 With respect to lower esophagus sphincter (LES) pressure, PGs and NSAIDs have little effect on LES pressure and motility of the esophageal body. NSAIDs do not provoke gastroesophageal reflux in the pathogenesis of esophageal ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the human esophagus, however, the main pathway for prostaglandin (PG) synthesis is reported to involve lipoxygenase rather than cyclooxygenase. 15 With respect to lower esophagus sphincter (LES) pressure, PGs and NSAIDs have little effect on LES pressure and motility of the esophageal body. NSAIDs do not provoke gastroesophageal reflux in the pathogenesis of esophageal ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, esophageal cell proliferation increased in the biliopancreatic and pancreatic reflux model [33]and Miwa et al [34]reported that reflux of duodenal or gastroduodenal contents in rat models induced esophageal adenocarcinoma, adenosquamous carcinoma and squamous cell carcinoma. Ottignon and Deschamps [35]reported that patients with both erosive and nonerosive reflux esophagitis exhibit increased levels of PGE 2 , PGF 2α and PGD 2 in esophageal mucosa derived from endoscopic pinch biopsies compared to healthy controls. However, they did not refer to COX-2 expression in these samples.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies in human subjects has increased lately, yet few have addressed the role of prostaglandins in the human esophagus and jejunum. [1][2][3][4][5][6] The increase in the number of cases of inflammatory bowel disease (IBD) in recent years has also drawn more attention to the pathophysiology of the small bowel. We set out to determine the mucosal prostaglandin content in normal healthy subjects and also in inflammatory conditions in these two rarely investigated segments of the human alimentary tract.…”
Section: Introductionmentioning
confidence: 99%